Effects of varying fertilization rates on morphological and mechanical characteristics of rice MR263 grown on rice husk ash (RHA) engineered alluvial soils - Nur Hidayah, Awang (Universiti Malaysia Perlis (UniMAP), 2016)
Access is limited to UniMAP community.